Use of the Geodimeter by the Coast and Geodetic Survey - Thomas, Paul D. (The International Hydrographic Review, 2018)
The Coast and Geodetic Survey has measured 84 geodetic lines with the Geodimeters, Models 1 and 2, over a five-year period. Based on this experience, a routine of field operations has been developed and a manual of operation is being prepared. Maintenance problems have been negligible and only minor modifications of the instruments have been made. The Coast and Geodetic Survey recommends the Geodimeters (Model 1 or 2) for measuring first-order triangulation baselines, trilateration, traverse, and for calibrating electronic distance-measuring equipment such as the Tellurometer.